GASTON: Galactic Star Formation with NIKA2 – evidence for the mass growth of star-forming clumps. Issue 3 (25th January 2021) - Rigby, A J; Peretto, N; Adam, R; Ade, P; Anderson, M; André, P; Andrianasolo, A; Aussel, H; Bacmann, A; Beelen, A; Benoît, A; Berta, S; et al.
ABSTRACT: Determining the mechanism by which high-mass stars are formed is essential for our understanding of the energy budget and chemical evolution of galaxies. By using the New IRAM KIDs Array 2 (NIKA2) camera on the Institut de Radio Astronomie Millimétrique (IRAM) 30-m telescope, we have conducted high-sensitivity and large-scale mapping of a fraction of the Galactic plane (GP) in order to search for signatures of the transition between the high- and low-mass star-forming modes. Here, we present the first results from the Galactic Star Formation with NIKA2 (GASTON) project, a Large Programme at the IRAM 30-m telescope that is mapping ≈2 deg 2 of the inner GP, centred on ℓ = 23_.^° 9, b = 0_.^° 05, as well as targets in Taurus and Ophiuchus in 1.15- and 2.00-mm continuum wavebands. In this paper, we present the first of the GASTON GP data taken, and present initial science results. We conduct an extraction of structures from the 1.15-mm maps using a dendrogram analysis and, by comparison to the compact source catalogues from Herschel survey data, we identify a population of 321 previously undetected clumps. Approximately 80 per cent of these new clumps are 70- μ m-quiet, and may be considered as starless candidates. We find that this new population of clumps are less massive and cooler, on average, than clumps that have already been identified. Further, by classifying the full sample of clumps based upon their infrared-bright fraction – an indicator of evolutionary stage – we find evidence for clump mass growth, supporting models of clump-fed high-mass star formation.